Tools to Support SMEs to Migrate to the Cloud: Opportunities and Challenges - da Silva Filho, Heleno Cardoso (2019)
The first author of this paper thanks for the Scholarship (T.O.B)-No BOL0731/2016 provided by the Research Foundation State of Bahia (FAPESB).